Conservation discourses and practices in large-scale corridor projects : the case of the Greenbelt of Fennoscandia - Florin, Ian (2018)
Over the past two decades, growing concerns have emerged about the limited capacity to achieve consequential conservation outcomes on a global scale with existing protected areas. In this context, large-scale conservation corridors – capable to mitigate the effects of habitat fragmentation on key ecosystem processes, according to their advocates – have gained prominence among scientists and protected areas practitioners. Building on literature in political ecology and geography and using qualitative content analysis, this paper analyzeshowandwhyindividual and collective actors frame, shape and leverage large-scale corridors. In doing so, it explores ideological and strategical motivations that justify – in Boltanski & Thévenot's terms – conservation discourses and practices in large-scale corridors projects. On the one hand, I look at conservation paradigms, scientific discourses and geographical imaginaries that inform stakeholder claims. On the other hand, I analyze how stakeholders adapt to funding opportunities and simplify their discourses to promote their work on the national or international level. This will, in turn, require to engage with a broader literature on the critique of modernity and neoliberalism. I use theGreenbelt of Fennoscandia (GBF) –a network of existing and planned protected areas near the borders of Finland, Norway and Russia, based on a memorandum of understanding signed in 2010 – as a case study. This research draws on approx. 80 semi-structured interviews with officials involved in the GBF and other related stakeholders (hunters, foresters…) in Finland and Norway, as well as a desk study. In examining controversies about the boundaries, the type of activities or the governance structure of the project, I describe how scientific discourses on ecological connectivity and different nature conceptions (hybrid, fluid) and figures) are used by stakeholders to justify their claims. Furthermore, I show how some stakeholders see their involvement in the project as a way to attract extra ...